“The Golden Age of Islam” - The History of The Caliphate - Ravhsanbekovna, Rakhmanova Odinakhon (Indonesian Journal Publisher, 2024)
The article provides brief information about the reign of the Abbasid Caliphate during five centuries, the socio-economic and political disagreements that occurred on the territory of the Caliphate, the role of the Abbasid Caliphs in the development of science and culture, from the history of their rise to power to their fall.